Attitudes of professionals from Psychosocial Care Centers towards alcohol, alcoholism, and alcoholics - José Gilberto Prates; Márcia Aparecida Ferreira de Oliveira; Heloísa Garcia Claro; Paula Hayasi Pinho; Gabriella de Andrade Boska; Ivan Filipe de Almeida Lopes Fernandes; Julia Carolina de Mattos Cerioni Silva (Rev Rene)
Objective: to assess the attitudes of professionals from Psychosocial Care Centers towards alcohol, alcoholism, and alcoholics. Methods: a cross-sectional evaluation study with 288 professionals from 12 healthcare services. Sociodemographic data, Patient Satisfaction Scale with Mental Health Services and Attitude Scale for alcohol, alcoholism, and alcoholics were collected. Results: the professionals who showed a more critical attitude towards their work routine and those who worked in the healthcare services for longer had positive attitudes towards alcohol, alcoholism, and alcoholics. Professionals from the administrative team and health technicians had more negative attitudes. Conclusion: the attitudes of professionals towards alcohol, alcoholism, and alcoholics, in general, are positive and were associated with longer working time in the field and the manifestation of disapproving situations with work.